MAKNA DAN FUNGSI PATUNG-PATUNG DI BUNDARAN CITRA RAYA KABUPATEN TANGERANG PROVINSI BANTEN (KAJIAN SEMIOTIKA CHARLES SANDERS PEIRCE) - Ilmi Solihat (Jurnal Membaca Bahasa dan Sastra Indonesia, 2017)
The statue is the work of three dimensional objects humans recognized specifically of art. Because, the statue has the length, width and height (volume)and can be enjoyed from all directions. The purpose of the creation  is to produce works of art that can last as long time. The basic materials used in any shape such as the human form, animals and plants or other forms of modification results. Citra Raya located in Cikupa Tangerang Regency has the slogan “the town tastefully”, Large-sized statues of gates wellcome to spread Citra Raya. Citra Raya has four concept road roundabout (looped). At the first roundabout, there is a statue of person dancing ballet with the fountain underneath, at the second roundabout there is a statue of three women who are sitting together. At the third roundabout there is a sculpture of family with a cat and a dog, at the roundabout fourth there are two women; one of which was holding durian. Citra Raya statues scattered across the roundabout 4 certanly has meaning ang function. With it, researchers examine on the meaning and function statues in Citra Raya Tangerang Banten by using the theory Semiotics of Peirce. This research method using qualitative method description. Data obtained by means of the observation object sculptures in Citra Raya, ably, and documentation. Interview done to informants who are deemed to know te ins and outs of roundabout statue in Citra Raya.